Are there multiple scaling regimes in Holocene temperature records? - Nilsen, Tine; Rypdal, Kristoffer; Fredriksen, Hege-Beate (Earth System Dynamics, 2016)
Published version. Source at http://dx.doi.org/10.5194/esd-7-419-2016 In this article it is discussed how temperature variability on centennial timescales and longer can be described in a simplistic way. By analysing the scaling in late Holocene temperature reconstructions and longer temperature records from Greenland and Antarctic ice cores, we find that the choice of model depends heavily on the data material and timescale one chooses to emphasize. Ignoring data beyond the Holocene seems plausible when predicting temperature, but not for other purposes.